A scrutiny into fiscal policy in the South African economy: A Bayesian approach with hierarchical priors - Lindokuhle Talent Zungu; Bongumusa P. Makhoba; Lorraine Greyling (Cogent Economics & Finance, 2022)
This study analyses the impact of fiscal policy on the South African economy during the period 1972Q1-2020Q2. The study adopted quarterly time series data to estimate a Bayesian Vector Autoregression (BVAR) model with the selection of hierarchical priors. The variables employed for empirical investigation included GDP, government expenditure, public debt, and gross fixed-capital formation. The results of the study show that an unexpected shock in government expenditure and public debt has a significant negative and persistent impact on economic growth in South Africa, while an unexpected shock in investment has a significant positive effect on economic growth. The findings suggest that escalating public expenditure and public debt lead to economic contraction. This implies that policy-makers ought to be cautious of excessive government expenditure and public debt to achieve fiscal consolidation. Policy-makers ought to focus on addressing structural challenges through the implementation of sound structural reform policies that aim to attract investment consistent with job creation, development and growth in South Africa's economy.
Keywords: 330; BVAR; economic growth; government expenditure; hierarchical priors; publicdebts